Interfaith Social Relations Among Muslim-Non-Muslim Students: Portraying Religious Harmony in the School - Nurul Ahsin; Titis Thoriquttyas; Wildan Nasrulloh (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2022)
This research aims to reveal: 1) How are the conditions of interfaith social interaction between Muslim and non-Muslim students at SMAN 1 Kandangan Kediri? 2) What is the role of Islamic education teachers in building interfaith social interactions between Muslim and non-Muslim students? 3) What is the impact of understanding interfaith social attitudes by Islamic education teachers on students? This research used a qualitative approach conducted at SMAN 1 Kandangan Kediri. The data were collected through observations, interviews, and documentation. Informants in this study were Islamic education teachers, students of SMAN 1 Kandangan Kediri, and Christian education teachers. Meanwhile, data analysis was carried out using data reduction, data presentation, and drawing conclusions. The results of this study revealed that 1) the condition of interfaith social interaction showed a quite harmonious attitude, and it did not show any indications leading to division. 2) Islamic education teachers played a key role as an example of a figure forming students' interfaith social attitudes. 3) The impact on students included being more democratic, wiser in performing religious rituals, a high social spirit, more solid in cooperation, and respecting and appreciating each other.